1974
DOI: 10.1159/000224994
|View full text |Cite
|
Sign up to set email alerts
|

Link between Carcinogenicity and Hepatic Metabolism of 7,12-Dimethylbenz(α)anthracene

Abstract: Inhibition of hepatic drug metabolism in the Sprague-Dawley rat by coumarin pretreatment or pregnancy reduced significantly the incidence of mammary tumors induced by 7,12-dimethylbenz(α)anthracene (DMBA) alone in untreated or nonpregnant animals. When DMBA injections were followed by coumarin treatment the rats remained unprotected against the carcinogen. These observations strongly support the conclusion that tumorigenesis by DMBA is probably due to its minor metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…The protective action of coumarin showed a dose-response relationship (table I). These findings agree with our earlier results [11,12], In four different studies extended over 3 years, using two different strains (Sprague-Dawley and Wistar albino rats) and a wide range of coumarin levels, a suppression of cancer was ob served without any apparent toxic side effects. No marked difference was found in the histologic structure of mammary tumors between untreated and coumarin-treated rats, it seems, therefore, that while coumarin reduced the incidence and yield of breast tumors and retarded their formation, it failed to influence the degree of anaplasia once the neoplasm had developed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The protective action of coumarin showed a dose-response relationship (table I). These findings agree with our earlier results [11,12], In four different studies extended over 3 years, using two different strains (Sprague-Dawley and Wistar albino rats) and a wide range of coumarin levels, a suppression of cancer was ob served without any apparent toxic side effects. No marked difference was found in the histologic structure of mammary tumors between untreated and coumarin-treated rats, it seems, therefore, that while coumarin reduced the incidence and yield of breast tumors and retarded their formation, it failed to influence the degree of anaplasia once the neoplasm had developed.…”
Section: Discussionsupporting
confidence: 93%
“…Parallel with the reduction of tumor incidence, coumarin brought about an inhibition of hepatic drug metabolism and an increase of serum prolactin (table II). The inhibitory action on DMBA-metabolism by coumarin was concordant with our previous report [11] and is similar to the protection provided by pregnancy against DMBA tumorigenesis [12]. It was an unexpected finding that the administration of coumarin increased serum prolactin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Naturally occurring coumarins (NOCs), (e.g. 3 and 8) induce mouse skin tumor initiation in a well-established model of multistage carcinogenesis [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the level of DMBA in the plasma was not determined, Dao's (1971) hypothesis cannot be ruled out. Feuer & Kellen (1974b) have also suggested that progesterone exerts its effect on DMBA carcinogenesis through its action on the liver. They found that induction of pregnancy (a progestational state) before DMBA administration significantly reduced the mammary tumour incidence.…”
Section: D)iscussionmentioning
confidence: 99%